2020
DOI: 10.1101/2020.07.01.179515
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

VELCRO-IP RNA-seq explores ribosome expansion segment function in translation genome-wide

Abstract: SUMMARYRoles for ribosomal RNA (rRNA) in gene regulation remain largely unexplored. With hundreds of rDNA units scattered across multiple chromosomal loci, it is not possible to genetically modify rRNA in mammalian cells, hindering understanding of ribosome function. Emerging evidence suggests that expansion segments (ESs), tentacle-like rRNA extensions that vary in sequence and size across eukaryotic evolution, may provide platforms for the binding of proteins and mRNAs. Here,… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…The evolution of the ribosome to facilitate the translation of a Hox mRNA reflects an additional, important layer of control that may have co-adapted species-specific changes to Hox gene expression underlying embryonic development. Beyond that, in a separate manuscript, we extended these findings and identified hundreds of mouse embryonic mRNAs translationally regulated in an ES9S-depedent manner by defining the mRNA interactome of ES9S-humanized ribosomes genome-wide (Leppek et al, 2020). Moreover, the modular activity of the Hoxa9 P4 stemloop to enhance translation initiation from any 5 0 UTR by 40S-binding, and particularly via the 3 0 18-nt motif (Figure 2), reflects, to our knowledge, the shortest sequence harboring ribosome-binding activity in itself.…”
Section: Discussionmentioning
confidence: 86%
“…The evolution of the ribosome to facilitate the translation of a Hox mRNA reflects an additional, important layer of control that may have co-adapted species-specific changes to Hox gene expression underlying embryonic development. Beyond that, in a separate manuscript, we extended these findings and identified hundreds of mouse embryonic mRNAs translationally regulated in an ES9S-depedent manner by defining the mRNA interactome of ES9S-humanized ribosomes genome-wide (Leppek et al, 2020). Moreover, the modular activity of the Hoxa9 P4 stemloop to enhance translation initiation from any 5 0 UTR by 40S-binding, and particularly via the 3 0 18-nt motif (Figure 2), reflects, to our knowledge, the shortest sequence harboring ribosome-binding activity in itself.…”
Section: Discussionmentioning
confidence: 86%
“…We statistically evaluated the dynamic enrichment of these 600 RBPs with each of the evaluated ribosomal complexes between steady state and upon translational challenge and ranked them based on preferential enrichment upon stress (Hoteling's Two Sample T2) Figure 1E, Table S1). The top five enriched RBPs were BZW1 (Kozel et al, 2016), AARS (Negrutskii and Deutscher, 1991), HMGB2 (Leppek et al, 2021), RBPMS, and KNOP1, of which all except RBPMS and KNOP1 (KNOP1 is reported to be in the nucleolus (Brecht et al, 2020)) are known regulators of translation, consolidating that our identification and prioritization criteria yield translational regulators. While RBPMS has never been reported as a regulator of translation, it has been suggested as a potential regulator of embryogenesis (Aguero et al, 2016;Gerber et al, 2002;Gerber et al, 1999).…”
Section: Rna Binding Protein Rbpms Is a Translation Machinery-associamentioning
confidence: 77%